1999
DOI: 10.1007/s004250050760
|View full text |Cite
|
Sign up to set email alerts
|

Poly(β-hydroxybutyrate) production in oilseed leukoplasts of Brassica napus

Abstract: Polyhydroxyalkanoates (PHAs) comprise a class of biodegradable polymers which offer an environmentally sustainable alternative to petroleum-based plastics. Production of PHAs in plants is attractive since current fermentation technology is prohibitively expensive. The PHA homopolymer poly(beta-hydroxybutyrate) (PHB) has previously been produced in leaves of Arabidopsis thaliana (Nawrath et al., 1994, Proc Natl Acad Sci USA 91: 12760-12764). However, Brassica napus oilseed may provide a better system for PHB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…The values obtained in this study were in line with other studies that looked at different plants, though the transformed genes and targeting techniques we used were not the same: 20-100 mg gFW Ϫ1 in Arabidopsis (Poirier et al 1992), 14% DW in Arabidopsis (Nawrath et al 1994), less than 10 mg gFW Ϫ1 in tobacco (Nakashita et al 1999), 0-7.7% FW in Brassica (Houmiel et al 1999), 4% FW in Arabidopsis (Bohmert et al 2000), 2 to 8 ppm DW in tobacco (Nakashita et al 2001), maximal values of 3.2 mg gDW Ϫ1 in tobacco, 0.09 mg gDW Ϫ1 in potato, and 132 mg gDW Ϫ1 in Arabidopis (Bohmart et al 2002), 1.7% DW in tobacco (Lössl et al 2003), 55 mg gDW Ϫ1 in sugar beet (Menzel et al 2003), and 4.62 mg gFW Ϫ1 in flax (Wróbel et al 2004). It has been reported that growth retardation often accompanies the transformation, as is the case in tobacco (Lössl et al 2003).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The values obtained in this study were in line with other studies that looked at different plants, though the transformed genes and targeting techniques we used were not the same: 20-100 mg gFW Ϫ1 in Arabidopsis (Poirier et al 1992), 14% DW in Arabidopsis (Nawrath et al 1994), less than 10 mg gFW Ϫ1 in tobacco (Nakashita et al 1999), 0-7.7% FW in Brassica (Houmiel et al 1999), 4% FW in Arabidopsis (Bohmert et al 2000), 2 to 8 ppm DW in tobacco (Nakashita et al 2001), maximal values of 3.2 mg gDW Ϫ1 in tobacco, 0.09 mg gDW Ϫ1 in potato, and 132 mg gDW Ϫ1 in Arabidopis (Bohmart et al 2002), 1.7% DW in tobacco (Lössl et al 2003), 55 mg gDW Ϫ1 in sugar beet (Menzel et al 2003), and 4.62 mg gFW Ϫ1 in flax (Wróbel et al 2004). It has been reported that growth retardation often accompanies the transformation, as is the case in tobacco (Lössl et al 2003).…”
supporting
confidence: 88%
“…These genes are found in many species of bacteria (see review by Madison and Huisman 1999), and the transfer of genes from bacteria to plant cells has been demonstrated (Poirier et al 1992). Although there are many reports about PHB production in transgenic plants, the levels of PHB accumulation have fallen short of expectations: 14% DW is the highest level reported in Arabidopsis (Nawrath et al 1994), Ͻ10 mg gFW Ϫ1 in tobacco (Nakashita et al 1999), 1-1.7% DW in Brassica napus (Houmiel et al 1999), and 4-5 mg gFW Ϫ1 in flax (Wróbel et al 2004). In addition, plant growth has reportedly been inhibited because of depletion of the available pool of acetyl-CoA (Lössl et al 2003).…”
mentioning
confidence: 99%
“…The use of transgenic plants for bulk PHA accumulation seems attractive because of the expected low cost of production compared to microbial fermentative PHA production (Nawrath et al 1995). However, until now, most of the reports describing the production of PHAs in plants have focussed on polyhydroxybutyrate (PHB) biosynthesis (Poirier et al 1992;Nawrath et al 1994;John and Keller 1996;Hahn et al 1999;Houmiel et al 1999;Nakashita et al 1999;Slater et al 1999) whose range of applications is limited compared to that of mcl-PHAs. Until recently, knowledge of mcl-PHA biosynthesis was incomplete, which hampered the identification of the minimum gene-set required for its production in recombinant hosts.…”
Section: Discussionmentioning
confidence: 99%
“…At present, they are also used to produce biodiesel, as well as rubber and plastics (Kimber and McGregor 1995;Houmiel et al 1999). Brassica rapa (2n = 20, AA) is believed to be one of the diploid progenitor species of the amphidiploid B. napus (2n = 38, AACC).…”
Section: Introductionmentioning
confidence: 99%